Strategic Synthesis of Asymmetrically Substituted C4N4 Fluorophores - Xu, Wei; Kohei, Miki; Shibasaki, Masakatsu; Kumagai, Naoya (Synthesis, 2021)
C4N4 fluorophores comprise a recently disclosed new class of emissive organic molecules with modular synthetic capabilities. Herein, we report a new synthetic protocol toward asymmetrically diarylated C4N4 fluorescent materials. Direct monoarylation of 1-naphthol is exploited to suppress undesired diarylation and to provide a free phenolic hydroxy group for prospective linking to a molecule of interest. Installation of the second aromatic unit in order to acquire fluorescent properties is achieved by Suzuki–Miyaura cross-coupling.
Keywords: fluorescence; pyrimidine; quantum yield; aluminum; direct arylation; C4N4 fluorophore; fluorescent probe